2018
DOI: 10.1371/journal.pone.0203877
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing conflict between humans and big cats Panthera spp: A systematic review of research trends and management opportunities

Abstract: Conservation of big cats (Panthera spp.), a taxonomic group including tigers, lions, jaguars, leopards and snow leopards, is a daunting challenge. As expanding human populations across Panthera range countries exacerbate competition for land and prey, conflicts between humans and big cats are inevitable. Through a systematic review of the peer-reviewed literature published from 1991 to 2014 and indexed in Web of Science and Google Scholar (186 articles), our study explored the current state of knowledge regard… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
47
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(49 citation statements)
references
References 88 publications
(155 reference statements)
2
47
0
Order By: Relevance
“…Interactions between many mammalian carnivores and humans typically involve competition for resources as a result of carnivore species' predisposition for large home ranges and a dietary reliance on animal tissue (Thorn et al, 2012). It follows that the most common cause of human conflict over carnivores is livestock depredation (Krafte Holland et al, 2018;Torres et al, 2018). This leads to the persecution of carnivores in retaliation for livestock losses or as part of lethal control methods, and is the main reason many species are classified as Vulnerable, Endangered, or Critically Endangered (IUCN, 2016), but equally, threatens the sustainability of many agricultural practices around the world (Baker et al, 2008;Van Eeden et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interactions between many mammalian carnivores and humans typically involve competition for resources as a result of carnivore species' predisposition for large home ranges and a dietary reliance on animal tissue (Thorn et al, 2012). It follows that the most common cause of human conflict over carnivores is livestock depredation (Krafte Holland et al, 2018;Torres et al, 2018). This leads to the persecution of carnivores in retaliation for livestock losses or as part of lethal control methods, and is the main reason many species are classified as Vulnerable, Endangered, or Critically Endangered (IUCN, 2016), but equally, threatens the sustainability of many agricultural practices around the world (Baker et al, 2008;Van Eeden et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…In spite of a relative paucity of empirical evidence regarding HWC mitigation method effectiveness, one of the most successful methods documented is livestock guarding dogs (LGDs) (Eklund et al, 2017;Krafte Holland et al, 2018;Shivik, 2004;Torres et al, 2018;Van Eeden et al, 2018). Generally, LGDs are bred and trained to stay with the livestock herd and prevent carnivores from attacking through protective displays, often without physical conflict (Allen et al, 2017;Gehring et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…This may guide researchers and practitioners in considering the (in)effectiveness of particular interventions for their target species. Earlier, Krafte Holland et al (2018) compared the effectiveness only between interventions and not between the five big cat Panthera species what makes our results incomparable. We re‐analyzed 39 papers used by these authors in their study and found out that only eight of them provide quantitative information on evidence‐based effectiveness in compliance with our criteria (see Section 2).…”
Section: Discussionmentioning
confidence: 66%
“…Future collaborations must include both the ecological and the social-cultural dimensions of conservation. As well as investing in ways to strengthen the relationship between people and wildlife, building a relationship of trust and dialogue between conservation initiatives and distinct interest groups is paramount, and requires interdisciplinary team work (Carter and Linnell 2016;Holland et al 2018). Ecological research alone is not enough to slow down the loss of biodiversity.…”
Section: Finding Ways To Move Forwardmentioning
confidence: 99%